The analgesic efficacy of IV acetaminophen for acute postoperative pain in C-section patients: a randomized, double-blind, placebo-controlled study. (4th March 2022) - Bernstein, Jeffrey; Spitzer, Yelena; Ohaegbulam, Kim; Reddy, Shamantha; Song, Jing; Romanelli, Erik; Nair, Singh
Abstract: Background: The rate of cesarean delivery is on the rise in the USA. Satisfactory postoperative analgesia remains a top priority for cesarean delivery. Multimodal analgesia with a reduction in opioid consumption and improvement in patient satisfaction is a goal for anesthesiologists caring for this patient population. Our study sought to assess whether IV acetaminophen in four divided doses over 24 h decreased pain scores and opioid requirements in patients undergoing cesarean delivery with neuraxial anesthesia. Methods: 66 patients undergoing elective cesarean delivery under spinal anesthesia with hyperbaric bupivacaine 12 mg, fentanyl 10 µg, and preservative-free morphine 150 µg were randomized to receive either IV acetaminophen or IV placebo for four consecutive doses in the first 24 h postoperatively. The need for rescue medication using morphine equivalence, pain scores, patient satisfaction, and side effects were assessed by a blinded researcher in the first 24 and 48 h postoperatively. Results: There was no difference in opioid requirements in the acetaminophen versus placebo group, 44.32 ± 23 mg versus 47.59 ± 28 mg ( p = .607), respectively at 24 h. There was also no difference at 48 h, 57.95 ± 20 mg versus 56.59 ± 22 mg ( p = .795). Postoperative pain scores, patient satisfaction, and adverse events were similar in both groups as well. Conclusions: The results of this study failed to demonstrate any additional benefits of administering multiple doses of IV acetaminophen for treating postoperative pain in patients who have undergone CS surgery and receiving intra-thecal morphine as part of their anesthesia and analgesia. Trial Registry number: NCT02069184